Correlations of androstenediol with reproductive hormones and cortisol according to stages during the menopausal transition in Japanese women. Issue 214 (November 2021) - Kawakita, Takako; Yasui, Toshiyuki; Yoshida, Kanako; Matsui, Sumika; Iwasa, Takeshi
Highlights: DHEA-S and testosterone showed positive correlations with androstenediol in perimenopausal. Estradiol showed negative correlations with androstenediol in the menopausal transition. Cortisol showed positive correlations with androstenediol in the mid and late reproductive stage. Androstenediol may play a compensatory role for estrogen deficiency. Abstract: Associations of androstenediol, which has both androgenic and estrogenic activities, with circulating reproductive hormones and stress hormone in women during the menopausal transition may be different depending on the menopausal stage. The aim of this study was to determine the changes in circulating androstenediol during the menopausal transition in Japanese women and the associations of androstenediol with estrogen, androgen and cortisol for each stage of the menopausal transition. We divided the 104 subjects into 6 stages by menstrual regularity and follicle-stimulating hormone level: mid reproductive stage, late reproductive stage, early menopausal transition, late menopausal transition, very early postmenopause and early postmenopause. Levels of dehydroepiandrosterone sulfate (DHEAS), estradiol, estrone, testosterone (T), free T, androstenedione and cortisol were measured. Serum androstenediol concentration was measured by using liquid chromatography mass spectrometry. There were no significant differences in androstenediol levels among the 6 stages. Levels of DHEA-S and testosterone showed significant and positive correlations with androstenediol in all stages. Estradiol levels showed negative correlations with androstenediol levels in the late menopausal transition and very early postmenopause (r=-0.452, p = 0.052 and r=-0.617, p = 0.006, respectively). Cortisol levels showed significant and positive correlations with androstenediol levels in the mid and late reproductive stages (r = 0.719, p = 0.003 and r = 0.808, p < 0.001, respectively).The associations of androstenediol with estradiol and cortisol were different depending on the stage of the menopausal transition. Androstenediol may play a compensatory role for estrogen deficiency from late menopausal transition to very early postmenopause.